The influence of insulation of walls of industrial objects on thermal regime at the heating system of gas infrared radiators; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Nagornova T. A. Tatiana Aleksandrovna (2017, 2017)
Title screen